Laser Acupuncture Reduces Body Fat in Obese Female Undergraduate Students - Xiao-Guang Liu; Juan Zhang; Jian-Liang Lu; Timon Cheng-Yi Liu (International Journal of Photoenergy)
The purpose of this study was to investigate the efficacies of laser acupunctures with different laser irradiation doses for body weight loss and body fat reduction in obese persons. Twentyeight subjects with simple obesity were divided into four groups receiving laser acupunctures at 0, 358, 478, and 597 J/cm2, respectively, which were applied to the acupoints of Cv 8, St 25, and Sp 15, six times per week for four weeks. Body weight (BW), body mass index (BMI), body fat mass (BFM), body fat percent, waist girth, hip girth, and waist-to-hip ratio (WHR) were measured before and after treatment. The laser groups receiving 358 and 597 J/cm2 showed significant reductions in BW, BMI, BFM, waist girth, hip girth, and WHR after treatment compared with the placebo group. The percent reductions of BFM in the laser groups receiving 358 and 597 J/cm2 were 4.29% and 3.94%, respectively, and the corresponding values of BW were 1.99% and 1.63%, respectively. In conclusion, laser acupuncture could reduce body fat mass and lower body weight in a dose-dependent manner in obese persons. Among the doses of 358, 478, and 597 J/cm2, both the 358 and 597 J/cm2 doses were effective in the 4-week trial.